Dichrooscytus fervens sp. n., a new species of Miridae (Hemiptera, Heteroptera) from Finland - Muinonen, Arto; Rinne, Veikko; Vesterinen, Eero (Entomologica Fennica, 2019)
Dichrooscytus fervens Muinonen & Rinne sp. n. (Hemiptera: Heteroptera: Miridae) is described based on material collected in Finland between 2011 and 2018. A morphological description is provided along with DNA barcodes (COI gene) and a phylogeny of all the Dichrooscytus species for which a DNA barcode is available. The new species lives on Picea spp. and is still known only from Finland. A map of all the records is given, as well as an identification key of the Dichrooscytus species occurring in northern Europe.